ESTIMATES OF COILIA DUSSUMIERl POPULATION ALONG THE NORTHWEST COAST OF INDIA USING COHORT ANALYSIS - Fernandez, Irene; Devaraj, M (Indian Journal of Fisheries, 2011)
Cohort analysis for the Coilia ditssumieri stock along the northwest coast(Maharashtra and Gujarat coasts) of India for 1981-1983 indicated annual recruitsto be ranging from 5.1 x 10' to 6.8 x IC (mean = 5.7 x 10'*) and the spawnersfrom 3.1 X 10» to 4.2 x 10» mean. 3.55 x 10«). The annual yield ranged from16,353 t to 19,610 t (mean - 17,534 t). The fully recruited group of i + year(6 to 11 mon. fish), which was the age at first maturity as well as for maximumexploitation, formed the mainstay of the fishery. The present yield per recruit(Y|R = 3.0 g, for the annual exploitation ratio, E = 0.51 and the age at firstcapture, tc = 0.6 year) is close to the maximum Y|R of 3.04 g at E • 0.6;suggesting that only marginal increase in yield is possible by increasing the effort.At the present level of exploitation (51%), the effective fishing effort is about1,300 trawlers per day (Maharashtra = 740; Gujarat = 560) and about 2,000dol netters per day (Maharashtra = 1,200; Gujarat = 800) for about 215fishing days per year. The fishing effort seems to have remained around thislevel since 1971 obviously because of near-optimum level of yield from nearlyall the inshore stocks including that of C. dussumieri.